The peculiarities of health-related quality of life in recreational and competitive athletes - Tilindiene, I.; Petkune, L.; Ivanauskas, D. (Baltic Journal of Sport and Health Sciences, 2021)
Background. The scientific literature focuses on the evaluation of quality of life (QL) and health-related quality of life (HRQL) among recreational and competitive athletes. Research suggests that the QL and HRQL levels of competitive athletes can be negatively affected in that they spend most of their lives in training, preparing for and recovering from competitions and tournaments; however, they neither learn most of the essential life skills (Ohlert & Ott, 2017), nor allot time to their leisure activities and recreation. There are also contradictory studies indicating that competitive athletes evaluate HRQL better than recreational ones do (Lorcan & Allen, 2018; Pacesova, Smela, & Antala, 2019). However, little is known about the impact of how different levels of sports activities affect HRQL in this pandemic period.